National Border in the Classification of Literature: A Relevant or Outdated Category? - Stehlík, Petr (Poznańskie Studia Slawistyczne, 2025)
The aim of the paper is to reflect on the relevance of the concept of national literature from the perspective of the 21st century, to present methodological shortcomings and problematic aspects of the establishment of national borders in the delimitation of the literary field, and to consider the possibilities of overcoming a nationally determined approach to literature. The conclusions are presented using examples from the South Slavic literary corpus and processes. The author distinguishes three modes of relationship between literature and national ideology, in which the former functions as 1) a source, 2) a disseminator, and 3) an emblem of national identity. He calls for relegating the most controversial third mode to the field of historical research, proposes redefining the national border as a point of fruitful exchange between neighbouring literary traditions, and advocates conceptualizing new transnational or anational approaches to classifying literature, most notably in the post-Yugoslav space.